Pengaruh Kualitas Pelayanan, Fasilitas dan Brand Image Terhadap Kepuasan Pasien Di Klinik RH Medica Malang - Risca Trisnawati; Fathorrahman; Theresia Pradiani (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
Outpatient clinics in Indonesia, especially in Malang, continue to increase, one of the clinic services that is starting to develop is beauty. Looking beautiful and attractive is a need that always exists in every human being, especially women. The need to perform facial and body care to make it beautiful has had many positive impacts on the growth and development of clinics, one of which is RH Medica clinic in Malang. The purpose of this research is to analyze the effect of service quality, facility, brand image on patient satisfaction at RH Medica clinic. The subjects in this study were patients who visited, bought and used products/treatments with a sample of 98 respondents. Data collection techniques using a questionnaire. The analytical method used was descriptive analysis using non-probability techniques with purposive sampling, SPSS analysis method. using non-probability techniques with purposive sampling, SPSS analysis method. The results of this study show that service quality, facilities and brand image have a positive and significant effect on patient satisfaction at the RH Medica clinic. Simultaneously service quality, facilities and brand image have a significant effect on patient satisfaction at the RH Medica clinic, and patient satisfaction can be explained by the service quality, facilities and brand image variables of 68.4% while the rest is explained by other variables not present in this study.